Biologia e ecologia de crustáceos decápodos (Caridea e Brachyura) do infralitoral não consolidado da costa sudeste do Brasil - Pereira, Rafaela Torres [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The specimens of Nematopalaemon schmitti were captured in southeastern Brazil from 2008 to 2011, for reproductive output (RO) and fecundity analysis of species. Changes in the egg development associated to the ovary maturation of ovigerous female were also analyzed in order to verify possible synchronous relationship between them. Obtained ovigerous females were measured (carapace length [CL]) and analyzed as the stage of development of their ovaries and eggs. The RO was calculated based on dry weight of eggs and female masses. Fecundity was expressed by the equation obtained from regression between egg numbers and CL. A significant relationship was observed between the number of eggs and CL (p<0.001), showing that as higher is the female higher is its capacity to produce eggs. Comparing the mean number of eggs in stages I and II in N. schmitti, became evident a loss of 7% of eggs. Females with rudimentary ovaries showed, predominantly, eggs in stage I and females with developed ovaries showed only eggs in stage II, showing synchrony between the developing of both, thus supporting the hypothesis of a continuous reproductive cycle for N. schmitti in the study region. The RO and fecundity can be affected for biotic and abiotic factors, as parasites and variations in the latitudinal gradient. Informations of the reproductive output and its relations with the synchrony between the gonadal and embryonic development are rare for the palaemonoid shrimps, although they are crucial in understanding the reproductive biology of these animals, as well as other caridean shrimps
Keywords: Biodiversidade; Decapode (Crustaceo) - Distribuição geográfica; Reprodução animal; Zoologia - Pesquisa; Biodiversity